Analisis Motivasi Belajar Siswa Terhadap Hasil Belajar IPAS Siswa Kelas IV SD Negeri 61 Lubuklinggau - Feni Atari Gumai; Sulistiyono; Supriyanto (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to determine the effect of the Relating, Experiencing, Applying, Cooperating, Transferring (REACT) learning model on motivation and learning outcomes of fourth-grade students at SD Negeri 61 Lubuklinggau. The method used was an experimental research design involving two sample groups, namely an experimental group that received instruction using the REACT learning model and a control group that received conventional learning. Based on a preliminary study conducted in September 2025 at SD Negeri 61 Lubuklinggau, the learning process was still dominated by the lecture method. This condition tended to cause students to feel bored, resulting in low interest in participating in learning activities. Consequently, the expected learning objectives were not achieved optimally. This was indicated by the average score of the odd-semester daily test in Indonesian language subjects for fourth-grade students in the 2025/2026 academic year, which was still below the Minimum Mastery Criteria (70), with an average score of 65.94. Out of 18 fourth-grade students, only 6 students achieved the Learning Objective Achievement Criteria, while 12 students did not meet the minimum criteria. Keywords: Learning Outcomes, Motivation, Relating, Experiencing, Applying, Cooperating, Transferring (REACT)